Working with families in youth justice - Trotter, Christopher John (Probation journal, 2017)
There is considerable evidence that family relationships are a factor in youth offending and that working with families of young offenders can improve family relationships and reduce the likelihood of re-offending. There is less evidence that frontline youth justice staff can successfully deliver family interventions to the families of young people on court orders. This study examines a project which involves the delivery of collaborative family work by youth justice workers in New South Wales, Australia, to young people and their families as part of a statutory youth justice service. The paper first outlines the literature, which supports the value of working with the families of young offenders. It then outlines the aims and methodology of the study followed by a discussion of the results, limitations and implications.